2019
DOI: 10.1029/2019gl082943
|View full text |Cite
|
Sign up to set email alerts
|

ENSO Regime Changes Responsible for Decadal Phase Relationship Variations Between ENSO Sea Surface Temperature and Warm Water Volume

Abstract: The relationship between the equatorial Pacific warm water volume (WWV) and El Niño–Southern Oscillation (ENSO) sea surface temperature (SST) has varied considerably on decadal timescales. These changes are strongly related to the occurrence frequency of central Pacific (CP) ENSO events. While both eastern Pacific (EP) and CP ENSO events show clear signatures of WWV recharge/discharge, their phase‐lag relationships between WWV and Niño3.4 SST are different. The WWV usually leads the Niño3.4 SST by two to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
(58 reference statements)
6
26
0
Order By: Relevance
“…The peak correlation coefficient between these two indices decreases from 0.75 before 2000 to 0.66 after 2000 (significant at the 95% confidence level), and the time by which WWV leads the Niño3.4 index also decreases (from seven to four months). These results indicate that the WWV, the dominant signal from the tropical Pacific, is not sufficient to predict ENSO variation after 2000, in agreement with previous studies (Horii, Ueki, and Hanawa 2012;Clarke 2014;Neske and Mcgregor 2018;Zhang et al 2019).…”
Section: Resultssupporting
confidence: 90%
“…The peak correlation coefficient between these two indices decreases from 0.75 before 2000 to 0.66 after 2000 (significant at the 95% confidence level), and the time by which WWV leads the Niño3.4 index also decreases (from seven to four months). These results indicate that the WWV, the dominant signal from the tropical Pacific, is not sufficient to predict ENSO variation after 2000, in agreement with previous studies (Horii, Ueki, and Hanawa 2012;Clarke 2014;Neske and Mcgregor 2018;Zhang et al 2019).…”
Section: Resultssupporting
confidence: 90%
“…ENSO predictability has experienced a pronounced shift around 2000 with a skillful lead time decrease from about three seasons to one season (Hendon et al, 2009;McPhaden, 2012;W. Wang et al, 2010), which has been attributed to an ENSO regime shift with more frequent CP El Niño events occurring post-2000 (Zhang et al, 2019). The seasonal prediction of Australian precipitation is expected to struggle with the significantly reduced ENSO predictability in recent decades (Hendon et al, 2009;W.…”
Section: Discussionmentioning
confidence: 99%
“…ENSO is further energized by stochastic atmospheric forcing 7 and modulated by the seasonal cycle 8,9 . Counterintuitively, despite significant advances in both ENSO theory and ENSO representation in climate models, the predictability of central-to-eastern tropical Pacific SST anomalies has decreased in the past two decades to only one season [10][11][12] . Research over the past years has further revealed that SST anomalies in other ocean basins may also play an important role shaping the evolution of El Niño events and its predictability [13][14][15][16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%